Cationic antimicrobial peptide, magainin down-regulates secretion of pro-inflammatory cytokines by early placental cytotrophoblasts. Issue 1 (December 2015) - Anupa, G.; Bhat, M.; Srivastava, A.; Sharma, J.; Mehta, N.; Patil, Asmita; Sengupta, Jayasree; Ghosh, D.
Abstract Background Human placental villous cytotrophoblasts exhibit relative externalization of negatively charged moieties to the outer leaflet of the plasma membrane during the time of syncytialization rendering their reactivity to positively charged cationic antimicrobial peptides (CAMPs) during the window of implantation and early placentation. Vaginal administration of a synthetic CAMP, Ala8, 13, 18 -magainin II amide (AMA) inhibited blastocyst implantation and early placentation in monkeys. Furthermore, the administration of AMA resulted in significant inhibition of cell differentiation, enhancement in apoptosis and loss of viability in first trimester placental villous cytotrophoblasts in primary culture. The present study examines the effect of in vitro application of different doses (0, 1, 10, 100, 1000 ng/ml) of AMA on the secreted cytokine profiles of cytotrophoblasts obtained from placental villi samples (n = 13 ) collected during 8–9 weeks of gestation and grown on three-dimensional collagen matrix in vitro. Methods A panel of forty-eight (48) cytokines in conditioned medium was analysed using multiplex immunoassays technique. Further, the steady state transcript levels of four cytokines (CCL4, CCL5, IL1B, IL6), the concentrations of which were affected by AMA in the isolated cytotrophoblasts, as well as, two cytokines (IL1A and TNF) which were not affected by AMA were estimated. Input list of cytokines secreted by cytotrophoblasts and showing differential secretion in response to AMA were used in enrichment analysis for the generation of biological networks. Results Placental cytotrophoblasts secreted 27 cytokines, 13 of which are affected by AMA in vitro with significantly decreased secretion of CCLs-2, 3, 4, 5, CXCLs-1 and 8, FGF2 and MCSF and that of IL1B, IL6 and MIF, and increased secretion of IL16 and IL-2RA. Of the above cytokines showing differential secretion, only IL-2RA, IL16 and MIF showed significant correspondence in the steady state expression of their respective transcript levels. Post-hoc Enrichment analysis revealed Toll-like receptor (TLR) mediated pathways were the top-scored target pathways that were affected by AMA. Conclusions Administration of a CAMP causes shift in the balance of immune-inflammatory responses involving downstream pathways of TLRs in cytotrophoblast function. Further verification of functions of placental trophoblasts on administration of CAMP with pregnancy outcome is necessary.